A review on DC/DC converter architectures for power fuel cell applications. (15th November 2015) - Kolli, Abdelfatah; Gaillard, Arnaud; De Bernardinis, Alexandre; Bethoux, Olivier; Hissel, Daniel; Khatir, Zoubir
Highlights: Different DC/DC power converter topologies for Fuel Cell systems are presented. Advantages and drawbacks of the DC/DC power converter topologies are detailed. Wide-BandGap semiconductors are attractive candidates for design of converters. Wide-BandGap semiconductors improve efficiency and thermal limits of converters. Different semiconductor technologies are assessed. Abstract: Fuel cell-based power sources are attractive devices. Through multi-stack architecture, they offer flexibility, reliability, and efficiency. Keys to accessing the market are simplifying its architecture and each components. These include, among others, the power converter enabling the output voltage regulation. This article focuses on this specific component. The present paper gives a comprehensive overview of the power converter interfaces potentially favorable for the automotive, railways, aircrafts and small stationary domains. First, with respect to the strategic development of a modular design, it defines the specifications of a basic interface. Second, it inventories the best architecture opportunities with respect to these requirements. Based on this study, it fully designs a basic module and points out the outstanding contribution of the new developed silicon carbide switch technology. In conclusion, this review article exhibits the importance of choosing the right power converter architecture and the related technology. In this context it is highlighted that the output power interface can be efficient, compact and modular. In addition, its features enable a thermal compatibility with many ways of integrating this component in the global fuel cell based power source.